Mucosa-associated lymphoid tissue lymphoma of the lachrymal gland: A case report - Nedeljkov-Jančić Ružica (Srpski Arhiv za Celokupno Lekarstvo, 2005)
Mucosa-associated lymphoid tissue (MALT) lymphoma has drawn attention in the last twenty years due to its pathological and clinical characteristics. It is a question of B-cell neoplasm with extranodal origin, and with invariable prolonged localization, indicating indolent malignancy. It is believed that this type of lymphoproliferative neoplasm is triggered by chronic antigenic stimulation. This is supported by the observation that this type of extranodal lymphoma is frequently found in regions affected by chronic inflammation, such as mucosa of the stomach, the respiratory tract, as well as of the salivary and the thyroid glands. It is not common in the breasts, liver, kidneys, and gallbladder. Primary orbital lymphomas account for 5-14% of all extranodal lymphomas. The most commonly involved orbital tissue structures are: conjunctiva, the eyelids, and retrobulbar tissue, while the development of the disease in the lachrymal gland is extremely rare. No wonder that the literature on the presentation, treatment modalities, and recommendations for the monitoring of MALT lymphoma of the lachrymal gland is so scarce. Given the aforementioned facts, the case report of a patient with primary localization of MALT lymphoma of the lachrymal gland was considered intriguing; initially, the patient was successfully treated by surgical intervention followed by radiation therapy (TD 30 Gy).